Management of Persistent Hymen with Hydrocolpos in a Crossbred Heifer - Thakur, Sachin; Ahuja, Ankit; Thakur, Depika; Sharma, Amit; Sood, Pankaj (The Indian Journal of Animal Reproduction, 2026)
This case report describes a crossbred heifer diagnosed with persistent hymen and hydrocolpos following repeated failed insemination attempts. Diagnosis was confirmed through trans-rectal ultrasonography and vaginal examination, and successful surgical hymenectomy restored fertility, leading to a full-term pregnancy and healthy calving.
Keywords: Persistent hymen; Hydrocolpos; Borescope